The Chinese Antarctic science programme: origins and development - Mengzhu Zhang; Marcus Haward (2022)
In 1980, at the invitation of Australia, the first Chinese scientists went to Antarctica. China was therefore a relative ‘latecomer’ to engage in Antarctic science. In the period since its first Antarctic expedition in 1984, China's presence in Antarctica has expanded both in terms of its logistics and infrastructure and its scientific research. This paper outlines the development of China's national Antarctic programmes under the influence of corresponding national policies from the late 1970s to the present, noting the application of various scientific disciplines to Antarctic fields. The paper outlines and analyses the broadening and deepening of China's Antarctic science research, infrastructure and engagement.